2021
DOI: 10.21203/rs.3.rs-1047141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is YouTube a Reliable Source of Health-Related Information? A Systematic Review 

Abstract: Background: You Tube is a valuable source of health-related educational material which can have a profound impact on people's health-related behaviors and decisions. However, YouTube contains a wide variety of unverified content that may promote unhealthy behaviors and activities. We aim in this systematic review to provide insight into the published literature concerning the quality of health information and educational videos found on YouTube.Methods: A search of peer-reviewed original articles was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Finding appropriate content on social media is a general challenge [210]- [212]. This task is complicated by the huge offer of content, the popularity-biased ranking by search and recommendation systems [6], [213], and the difficulty to assess content coverage or quality with-out watching the video. Some professional YouTubers provide descriptions for their videos but it is not clear whether learners make use of these descriptions before they decide to watch.…”
Section: How Is Youtube Used In Education and How Does It Affect Stud...mentioning
confidence: 99%
“…Finding appropriate content on social media is a general challenge [210]- [212]. This task is complicated by the huge offer of content, the popularity-biased ranking by search and recommendation systems [6], [213], and the difficulty to assess content coverage or quality with-out watching the video. Some professional YouTubers provide descriptions for their videos but it is not clear whether learners make use of these descriptions before they decide to watch.…”
Section: How Is Youtube Used In Education and How Does It Affect Stud...mentioning
confidence: 99%
“…A systematic review by Osman et al of 202 articles assessing 22,300 health-related YouTube videos found that about 41% of health-related content objectively assessed using standard scoring systems across a wide range of medical specialties was reported to be inaccurate or "not useful" while only about 19% of such content was categorized as useful, with more than half refecting commercial interests [16]. Te same study also revealed that 44% of articles highlighted the role of verifed health sources in promoting reliable information on YouTube with 11% discouraging the use of YouTube as a platform for promoting actionable health-related content.…”
Section: Introductionmentioning
confidence: 99%
“…If one understands that, according to social media management platforms, people globally watch over one billion hours of YouTube videos every day—we speak about two billion people—, 14 it is easy to understand that the low numbers, as well discussed by Penny‐Dimri et al 11 are a fundamental limitation of ML methods in predicting outcomes in cardiac surgery now. Of course, using YouTube as a reference or comparator is a silly approach for different reasons; the first and most important is that YouTube is not a reliable source of medical‐related information as appropriately documented by Osman et al 15 …”
mentioning
confidence: 99%